Epigenetic effects of in utero bisphenol A administration: Diabetogenic and atherogenic changes in mice offspring - Umbreen Bano; Samreen Memon; Muhammad Shahani; Pashmina Shaikh; Samina Gul (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): Bisphenol A (BPA) that is a monomer of plastic products may possibly interfere with epigenetics and be involved in onset and progression of several diseases. This study was aimed to detect the epigenetic effects of in utero BPA exposure in mice offspring.Materials and Methods: All experiments were performed according to the national guidelines for laboratory animals and after ethical approval. Thirty adult BALB/c female mice were divided into 3 equal groups, G1 (controls), G2 (ethanol 0.10 ml/100ml of PBS so that final concentration would be 0.01%) vehicle control and G3 (BPA 10 mg/kg). Chemicals were given twice a week throughout the pregnancy. Once delivered at term, female offspring were observed for body weight, behavior and movements. Blood glucose, serum insulin, cholesterol and high-density lipoprotein cholesterol (HDLc) were measured at 5 and 15 months postnatal. Animals were sacrificed at 15 months and pancreas, kidney, adipose tissue and uterine tissue were taken and stained with either Hematoxylin and eosin (H & E) or immunostaining and examined under light microscope.Results: Offspring of group G3 revealed abnormal changes of body weight, behavior and movements. Blood glucose, serum insulin, cholesterol and HDLc were high in group G3 offspring compared to controls. H & E staining showed changes in the parenchyma of pancreas, kidneys and uterus, which were confirmed by staining with anti- islet-1, kidney-specific (Ksp) cadherin, and anti- MLH antibody. Conclusion: In utero exposure of BPA exerts diabetogenic and atherogenic effects with less parenchymal tissue in endocrine pancreas, kidney and uterus.